Boosting knowledge on occupational exposure to microbial contamination in Portuguese carpentries - Dias, Marta; Gomes, Bianca; Pena, Pedro; Cervantes, Renata; Rodriguez, Margarida; Riesenberger, Bruna; Marques, Liliana; Carolino, Elisabete; Twarużek, Magdalena; Kosicki, Robert; Soszczynska, Ewelina; Caetano, Liliana Aranha; et al. (Frontiers in Public Health, 2025)
IntroductionWood industry workers face health risks due to exposure to microorganisms and their metabolites. This study aimed to characterize seasonal microbial contamination, antifungal resistance, mycotoxins, cytotoxicity, and particulate matter in Portuguese carpentries, to reduce exposure and promote safe working conditions.MethodsConducted in six carpentries in Lisbon, Portugal, the sampling strategy encompassed active and passive sampling methods to assess microbial contamination. A Handheld Particle Counter HH3016-IAQ was used to monitor particulate matter size, temperature, and humidity.ResultsThe highest fungal load was in the cold season, with Aspergillus sp. being the predominant species, and the highest bacterial load in the warm season. Reduced susceptibility to azoles was observed in both seasons, with greater species diversity in the cold season. In the warm season, Nidulantes and Fumigati sections of Aspergillus were detected by RT-PCR, with Fumigati being the most prevalent; in the cold season, only Nidulantes was detected. Mycotoxins, mainly fumonisins, were more prevalent in the warm season; in the cold season, griseofulvin was the most prevalent mycotoxin. Cytotoxicity was more prevalent in A549 cells than in SK cells. Settled dust caused greater cytotoxicity in SK cells, and filters from the vacuumed dust in A549 cells. Higher particulate matter concentrations in the indoor sampled areas suggest a significant contribution of indoor activities to workers’ exposure.DiscussionThe study highlights concern about seasonal variations in microbial contamination, emphasizing the potential for respiratory diseases, invasive infections by azole-resistant fungi, mycotoxin exposure, and cytotoxicity in lung cells due to co-exposure to fungi, particulate matter, and mycotoxins influenced by environmental conditions.